4R-Cembranoid Improves Outcomes after 6-Hydroxydopamine Challenge in Both In vitro and In vivo Models of Parkinson's Disease - Hu, Jing; Ferchmin, P. A.; Hemmerle, Ann M.; Seroogy, Kim B.; Eterovic, Vesna A.; Hao, Jiukuan (Frontiers in Neuroscience, 2017)
(1S, 2E, 4R, 6R,-7E, 11E)-2, 7, 11-cembratriene-4, 6-diol (4R) is one of the cembranoids found in tobacco leaves. Previous studies have found that 4R protected acute rat hippocampal slices against neurotoxicity induced by N-methyl-D-aspartate (NMDA) and against the toxic organophosphorus compounds paraoxon and diisopropylfluorophosphate (DFP). Furthermore, in vivo, 4R reduced the infarct size in a rodent ischemic stroke model and neurodegeneration caused by DFP. The present study expanded our previous study focusing on the effect of 4R in Parkinson’s disease (PD) and elucidating its underlying mechanisms using 6-hydroxydopamine (6-OHDA)-induced injury models. We found that 4R exhibited significant neuroprotective activity in the rat unilateral 6-OHDA-induced PD model in vivo. The therapeutic effect was evident both at morphological and behavioral levels. 4R (6 and 12 mg/kg) treatments significantly improved outcomes of 6-OHDA-induced PD in vivo as indicated by reducing forelimb asymmetry scores and corner test scores four weeks after injection of 6-OHDA (p<0.05). The therapeutic effect of 4R was also reflected by decreased depletion of tyrosine hydroxylase (TH) in the striatum and substantia nigra (SN) on the side injected with 6-OHDA. TH expression was 70.3% and 62.8% of the contralateral side in striatum and SN, respectively, after 6 mg/kg 4R treatment; furthermore, it was 80.1% and 79.3% after treatment with 12 mg/kg of 4R. In the control group, it was 51.9% and 23.6% of the contralateral striatum and SN (p<0.05). Moreover, 4R also protected differentiated neuro-2a cells from 6-OHDA-induced cytotoxicity in vitro. The activation of p-AKT and HAX-1, and inhibition of caspase-3 and endothelial inflammation were involved in 4R-mediated protection against 6-OHDA-induced injury. In conclusion, the present study indicates that 4R shows a therapeutic effect in the rat 6-OHDA-induced PD model in vivo and in 6-OHDA-challenged neuro-2a cells in vitro.